Comparison of three baseball-specific 6-week training programs on throwing velocity in high school baseball players - Escamilla, R. F.; Ionno, M.; de Mahy, M. S.; Fleisig, G. S.; Wilk, K. E.; Yamashiro, K.; Mikla, T.; Paulos, L.; Andrews, J. R. (The Journal of Strength and Conditioning Research, 2012)
Throwing velocity is an important baseball performance variable for baseball pitchers, because greater throwing velocity results in less time for hitters to make a decision to swing. Throwing velocity is also an important baseball performance variable for position players, because greater throwing velocity results in decreased time for a runner to advance to the next base. This study compared the effects of 3 baseball-specific 6-week training programs on maximum throwing velocity. Sixty-eight high school baseball players 14-17 years of age were randomly and equally divided into 3 training groups and a nontraining control group. The 3 training groups were the Throwers Ten (TT), Keiser Pneumatic (KP), and Plyometric (PLY). Each training group trained 3 d·wk-1 for 6 weeks, which comprised approximately 5-10 minutes for warm-up, 45 minutes of resistance training, and 5-10 for cool-down. Throwing velocity was assessed before (pretest) and just after (posttest) the 6-week training program for all the subjects. A 2-factor repeated measures analysis of variance with post hoc paired t-tests was used to assess throwing velocity differences (p < 0.05). Compared with pretest throwing velocity values, posttest throwing velocity values were significantly greater in the TT group (1.7% increase), the KP group (1.2% increase), and the PLY group (2.0% increase) but not significantly different in the control group. These results demonstrate that all 3 training programs were effective in increasing throwing velocity in high school baseball players, but the results of this study did not demonstrate that 1 resistance training program was more effective than another resistance training program in increasing throwing velocity.